Inter-related Factors Influencing Sexual Quality of Life among Women Living with HIV in Banten Province, Indonesia: A Mixed Methods Study - Juliastuti, Dyah; Dean, Judith; Afiyanti, Yati; Fitzgerald, Lisa (Kesmas, 2021)
Socio-cultural concerns often restrict women's sexual rights and well-being living with HIV (WLHIV) in developing countries. These convergent parallel mixed methods study combined quantitative and qualitative approaches to explore factors influencing WLHIV sexual quality of life in Banten Province, Indonesia. A 2017 cross-sectional survey of 207 reproductive-aged WLHIV was analyzed using univariate and multivariate logistic regression statistics. Furthermore, in-depth interviews with a sub-sample of survey participants (n = 30) were thematically analyzed. Most of the women (60%) involved reported loss of sexual pleasure and depressed sexual life. Meanwhile, 48% affirmed low sexual quality of life which was associated with unemployment (aOR = 2.90, and 95%CI =1.51–5.58), limited sexual activities (aOR = 2.89, and 95%CI = 1.20–6.93), living with extended family (aOR = 2.68, and 95%CI = 1.27–5.65), and experiencing intimate partner violence (aOR = 2.28, and 95%CI = 1.03–5.03). The respondents described unsatisfactory sexual life in a belief that having sex is a wife's duty and choosing not to talk about sexual issues or refuse sexual invitation in fear of triggering intimate partner violence. Inter-related personal, social, cultural, and religious factors affected the sufferers’ sexual life.